Reasons and Pattern of Demand for Root Canal Treatment Among Patients Attending A Tertiary Care Center of Madhesh Province: A Descriptive Cross-Sectional Study (Med Phoenix, 2023)
Introduction: Root canal treatment (RCT) for permanent teeth involves the use of biologically acceptable chemical and mechanical treatment of the root canal system to promote healing and repair of the peri radicular tissues. The aim of the study was to analyze the reasons and pattern of demand for root canal treatment among patients attending a tertiary care center of Madhesh Province, Nepal.Materials and Methods: This was a descriptive cross-sectional study of patients who received root canal treatment in the Department of Conservative Dentistry and Endodontics, National Medical College, Birgunj, Nepal between September 2022 and February 2023.The demographic and clinical data of patients were recorded and statistical analysis was performed using SPSS version 24. Association between the variables was analyzed by Fischer exact tests. P-value